FARMERS’ PERCEPTION ABOUT QUALITY OF MULTIMEDIA MODULES ON DAIRY FARMING PRACTICES - G. R. K. SHARMA2, T. VIJAYA NIRMAL (Indian Journal of Animal Production and Management, 2017)
Present study interprets the perception of dairy farmers about the quality ofmultimedia modules developed for the purpose along with the constraints faced andsuggestions voiced. The quality of multimedia modules were perceived with the help ofthe parameters related to attractiveness, holding interests, use of visuals and models,production skills and presentation skills. The results revealed that majority of the dairyfarmers had perceived that, the quality of multimedia modules are good and found to beuseful. But, lack of awareness was perceived as major constraint while usingmultimedia modules as information source. An awareness campaign at different placesat regular intervals will certainly help out to promote such multimedia modules asinformation source and that can be effectively used for disseminating technologies onvarious dairy farming practices.Key words: Perception, Multimedia modules, Dairy farmers